Lightweight real-time detection of sweet potato virus disease by a hybrid CNN–Transformer network - Ru Han; Lei Shu; Grzegorz Cielniak; Yan Zhu; Xing Yang; Fan Yang; Kai Huang (Computers and Electronics in Agriculture, 2026)

Hepatocyte necroptosis triggers macrophage NOD-like receptor family pyrin domain-containing 3 inflammasome activation in N, N-dimethylformamide-induced liver injury - Xiu-Ning Zhang; Jing-Jing Chen; Shuo Wang; Yan-Jing Zhang; Wei-Ru Wang; Tao Zeng (Toxicology, 2026)

Trem2 regulates macrophage phenotype via the JAK2/STAT3 signaling pathway to ameliorate ventricular remodeling after acute myocardial infarction - Zefeng He; Jing Feng; Ru Yan; Peng Wu; Baozhen Zhu; Huifang Li; Taoyu Yang; Yaxin Lu; Baotong He; Xueping Ma; Shaobin Jia; Guangzhi Cong (Molecular Biology Reports, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

From efficient nitrite accumulation to complete collapse: how a microbial community and its antibiotic resistance genes in a nitrification system respond to long-term exposure to ciprofloxacin and copper - Xiao-Yan Fan; Meng-Hao Hao; Jun-Ru Zhao; Xing Li; Shen-Bin Cao; Jia-Wei Ren; Ding-Chang Li (Journal of Water Process Engineering, 2026)

Uranium in-situ leaching: Combining conditional deep convolutional generative adversarial network (cDC-GAN) and ensemble smoother with multiple data assimilation (ES-MDA) to estimate the heterogeneous permeability coefficient field - Wen-gui Ji; Yue Luo; Bing Wang; Yi-ru Zhou; Yan-hong Zhang; Xian-ping Luo (Hydrometallurgy, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Temperature during vaccination shapes antibody responses and protection against infectious salmon anemia in Atlantic salmon under different prime–boost vaccine strategies - Manuel Soto-Dávila; Shona K. Whyte; Ruth L. Quispe; Yan-Ru Chen; Taylor Wheatley; Shawna L. Semple; Reza Ghanei-Motlagh; Eyesun Fajei; Eleanor Glahn; Frederick von Rönge; Andrew Swanson; Mark D. Fast (Fish & Shellfish Immunology, 2026)

Recyclable epoxy vitrimers based on multimechanism-activated transesterification strategies for photothermal conversion and self-healing materials - Huanyu Xu; Liangyi Xing; Ru Wang; Guiyu Chu; Yanmeng Peng; Zhiyue Zhao; Fengjiao Jiang; Shuhua Qi; Hongxia Yan (Chemical Engineering Journal, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Differential host choices of Helicoverpa armigera and H. assulta to tomato - Jie-Wen Mao; Qian-Wen Luo; Shao-Ting Duan; Meng-Hao Zhang; Xiao-Guang Liu; Xian-Ru Guo; Yan-Min Liu; Wei-Zheng Li (Arthropod-Plant Interactions, 2026)

Disentangling species-specific controls on urban tree transpiration: A Bayesian framework - Xiang Zhang; Xue Zhong; Jun-Ru Yan; Qi Li; Ling-Ye Yao; Kai-Xin Liu; Astrid Moser-Reischl; Thomas Rötzer; Stephan Pauleit; Mohammad A. Rahman (Agricultural and Forest Meteorology, 2026)

Complete mitochondrial genomes and phylogenetic analysis of three species of Indo-Pacific freshwater gobies, Stiphodon (Gobiiformes, Oxudercidae) - Cheng-He Sun; Xian-Ru Li; Su-Fan Zhou; Yan-Zi Zhong; Xiao Ma; Xiao-Die Chen (Journal of Genetics, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

On-site rapid detection method for Cryptolestes ferrugineus(Coleoptera: Laemophloeidae) based on recombinase polymerase amplification technology - Zhang Ru; Bai Yueliang; Bai Kaixu; Wang Hongjun; Zhao Chao; Yan Lei; Duangsamorn Suthisut; L.V. Jianhua; Zeng Fangfang; Zhang Meng; Bai Chunqi (Journal of Stored Products Research, 2026)

A hybrid deep learning framework for estimating urban tree transpiration - Xiang Zhang; Xue Zhong; Jun-Ru Yan; Qi Li; Kai-Xin Liu; Ling-Ye Yao; Long-Hao Zhang; Astrid Moser-Reischl; Thomas Rötzer; Stephan Pauleit; Mohammad A. Rahman (Journal of Environmental Management, 2026)

Sublethal cinnamon essential oil induces oxidative stress-driven metabolic reprogramming and attenuates spoilage potential in Psychrobacter faecalis - Yueping Yang; Ru Song; Pengcheng Li; Ye Tao; Xiaoyu Zou; Yan Xu; Rongbian Wei (Food Research International, 2026)

A macin family antimicrobial peptide from Atrina pectinata exhibiting dual functions in direct bactericidal activity and hemocyte immune modulation - Yan-ru Chen; Kun-yu Zhao; Shun-xin Hu; Ding-long Yang; Xue-peng Li; Li-zhu Chen; Jian-min Zhao (Fish & Shellfish Immunology, 2026)

Plasma-engineered chitosan couples red-light bioenergetics to diabetic wound regeneration through programmable microenvironments - Lekshmi Rethi; Hoa Duc Chau; Erlina Febriani; Yan-Ting Chen; Szu-Yu Tung; Pei-Ru Jheng; Yu-Wen Tseng; Rou Li; Min-Lang Tsai; Chun-Chi Chang; Van Khiet Pham; Hieu Trung Nguyen; et al. (Carbohydrate Polymers, 2026)

A comparative observational study of prokaryotic microbial community dynamics across different Litopenaeus vannamei cultivation systems - Chaosheng Zhou; Yue Wu; Maocang Yan; Rongmao Lu; Xiaolin Huang; Shaoguo Ru (Frontiers in Marine Science, 2026)
Introduction Microbial communities are key indicators of ecosystem health in aquaculture, yet their temporal dynamics under different cultivation systems remain poorly characterized. This study compares prokaryotic community succession across three commercial Litopenaeus vannamei cultivation systems with contrasting pond construction, salinity, and water-exchange intensity. Methods We collected 85 water samples from five sub-ponds per system at 15-day intervals and characterized prokaryotic communities via 16S rRNA amplicon sequencing, combined with α/β diversity, LEfSe, and PICRUSt2-based functional analyses. Results Community composition and diversity differed markedly among systems: α-diversity was highest in the earthen brackish pond (EBXS) and lowest in the concrete seawater pond (HSDT). Proteobacteria dominated all systems, while Actinobacteria prevailed in EBXS, which also showed increasing relative abundances of potentially pathogenic genera (Aeromonas, Mycobacterium, Rickettsia) over time. HSDT exhibited the highest predicted metabolic potential (90 enriched KEGG pathways). Temporally, EBXS displayed more stable succession and higher overall similarity, whereas high-level ponds showed greater species turnover. Discussion Salinity and cultivation system emerged as major correlates of community variation, though inherently confounded in our observational design. These patterns suggest a trade-off between community stability and pathogenic risk across production strategies. Our findings offer empirical baselines and testable hypotheses for future controlled studies to disentangle the individual effects of salinity, pond construction, and water management on microbial assembly in aquaculture systems.

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Facial width-to-height ratio predicts aggression and contest outcomes in wild golden snub-nosed monkeys - Pei Zhang; Yan-Ni La; Fei Niu; Jin-Bang Zhang; Paul A. Garber; Derek W. Dunn; Ru-Liang Pan; Kang Huang; Bao-Guo Li (Animal Behaviour, 2026)

Quantitative analysis of surrounding rock response considering the dynamic coupling evolution of 3D strength criterion parameters and seepage parameters - Zhiwei Yan; Ru Zhang; Zhilong Zhang; Zetian Zhang; Jing Xie; Anlin Zhang; Kun Xiao (Tunnelling and Underground Space Technology, 2026)

Paedocin A: An undescribed iridoid with a C1-C4 ether linkage from Paederia foetida with hepatoprotective effects - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry Letters, 2026)

Cadmium disrupts the immune antibacterial function of the freshwater crab Sinopotamon henanense via the Toll/proPO-AS pathway - Yue Liang; Duwen Pei; Cheng Liu; Fenjun Yan; Minnan Bao; Na Liu; Qian Wang; Caiping Feng; Ru Jia; Lan Wang (Journal of Hazardous Materials, 2026)

Divergent responses of soil respiration to reduced rainfall amount and frequency, and to nitrogen fertilization in a typical steppe - Lan Du; Yan Shen; Jiatao Zhang; Yonghong Luo; Jinbao Zhang; Ru Tian; Zhuwen Xu (Journal of Environmental Management, 2026)

Bioactivity assay coupled with molecular networking for the discovery of antioxidants from purslane - Yan-Xi Li; Mei-Ru Wang; Long-Gao Xiao; Huan Yan; Shan-Shan Ling; Hui Liu; Tao-Bin He; Wei Ni; Xin Fang; Hai-Yang Liu (Food Research International, 2026)

TRMT10A maintains lipid homeostasis independently of its tRNA m1G9 methyltransferase activity - Huihui Sun; Yu Wang; Shanpeng Liu; Yan Jin; Jianyang Ge; Bowen Zhang; Yongteng Wang; Weifeng Sun; Yun Bai; Yuyong Tao; Yi Lu; Ru-Juan Liu; et al. (Science China Life Sciences, 2026)

Scenario-based synergistic assessment of crop straw allocation for GHG mitigation and sustainable resource use in China - Yan Ru Fang; Zhongshi Tang; Xuefang Wu; Pingjian Yang (Sustainable Production and Consumption, 2026)

Comprehensive metabolic programming by enzymatic nanovesicle for acute kidney injury therapy - Yao Lei; Yuzhu Wu; Chao Li; Canwei Zou; Mingchuan Mao; Wan-Ru Zhuang; Yun Qu; Jiaqi He; Chao Liang; Weidong Nie; Hai-Yan Xie (Science Bulletin, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

Bioactive PVA/SDES propolis extracts composite films for extending oyster shelf life: Structure, functionality, and preservation performance - Tian Du; Lin-Kun Sun; Pei-Ru Zhou; Yu-Cang Zhang; Yan-Zhen Zheng (Food Packaging and Shelf Life, 2026)

Interpretable WTConv1D-BiLSTM monthly-scale precipitation prediction model based on novel multilevel and multi-scale decomposition - Menghao Wang; Rui Yan; Hongrui Wang; Ru Zhang; Yiyang Li (Atmospheric Research, 2026)

Study on the Diversity of the CXCL8 Family in Carassius auratus : Homologue Characteristics and Tissue‐Specific Immune Responses Under H. doneci Infection - Jin‐ye Zhang; Hong‐yan Liu; Yue‐ru Wang; Yuan‐jun Zhao (Journal of Fish Diseases, 2026)
Chemokines are essential for vertebrate immune regulation, and teleosts possess diverse CXCL8 lineages. However, studies on CXCL8 in C. auratus remain limited. In the present study, four CXCL8 homologues ( CaCXCL8‐1 to ‐4 ) were successfully cloned and identified from C. auratus , and their expression patterns were analysed in the tissues of healthy and those naturally infected with H. doneci . Bioinformatic analyses revealed that all homologues possess the conserved structural features of CXC chemokines. However, the divergence was observed in the N‐terminal ELR motif: CaCXCL8‐1 and CaCXCL8‐2 harboured a QLR motif, whereas CaCXCL8‐3 and CaCXCL8‐4 possessed a DPR motif. Phylogenetic analysis classified CaCXCL8‐1 and CaCXCL8‐2 into the CXCL8_L2 lineage, and CaCXCL8‐3 and CaCXCL8‐4 into the teleost‐specific CXCL8_L1b lineage. Tertiary structure predictions indicated that CaCXCL8‐1, −3, and −4 conserve key receptor‐binding sites, whereas CaCXCL8‐2 retained only GAG‐binding sites, suggesting potential functional divergence. Under healthy conditions, the four homologues were all constitutively expressed but displayed divergent basal profiles. Following H. doneci infection, they exhibited distinct tissue‐specific expression patterns: CaCXCL8‐1 was significantly upregulated in the gills; CaCXCL8‐2 was specifically induced in the spleen; CaCXCL8‐3 was markedly upregulated in both the gills and head kidney; and CaCXCL8‐4 was upregulated in the liver and head kidney but downregulated in the spleen. These divergent expression patterns suggest functional specialisation among the CaCXCL8 homologues, with different paralogs potentially coordinating localised versus systemic immune responses. Our findings provide evidence for the functional diversification of the CXCL8 chemokine in teleosts and contribute to understanding the evolution of complex immune systems in vertebrates.

Flos Trollii polyphenol-fortified noodles: Dual enhancement of textural properties and reduction of in vitro starch digestibility - Kebing Yan; Xianqing Ye; Xiaoai Zhu; Yuan Ru; Yage Liu; Yiying Niu; Jun Xi; Kunlun Liu (Journal of Cereal Science, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

Persimmon tannin: a novel green enhancer for dual improvement of texture and digestibility in surimi gels - Jingzhi Yan; Shiren Zhang; Kaile Chen; Yanxu Zhuang; Yiyi Cheng; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2026)

Ratio limitation of burnt-bitter-aroma compounds in strong-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Zheng-Juan Zhu; Jing Luo; Ling Xiang; Yan-Hong Xiang; Song-Tao Wang; Wen-Wen Zhang; Qing-Qing Liu; Ting Huang; Zheng-Hong Xu; Yong-Jun Yuan (Food Chemistry, 2026)

Unlocking the health co-benefits of the low-carbon transition: evidence from wind and solar power deployment in China - Ru Li; Yan Guo; Chen Zhang (Mitigation and Adaptation Strategies for Global Change, 2026)

Determining the age and size at sexual maturity in the sea cucumber Apostichopus japonicus - Siyi Yan; Zhaoyang Ma; Xiangyue Li; Xianjie Sui; Beini Deng; Jiaze Wang; Libin Zhang; Xiaoshang Ru (Aquaculture International, 2026)

Glial cell nutrient sensing: mechanisms of nutrients regulating Alzheimer’s pathogenesis and precision intervention - Qingmin Yan; Qihan Qin; Shu Zhang; Fuhao Chen; Yuehang Ru; Yi Zhong; Guoqing Wu (Critical Reviews in Food Science and Nutrition, 2026)

Polyhydroxypregnane glycosides and deoxyoligosaccharides from Cynanchum acutum subsp. sibiricum and anticomplementary activity of its compounds - Miao-Miao Li; Xue-Ru Wang; Wen-Jing Li; Zhi-Peng Zheng; Yan Lu; Qi Wang (Natural Product Research, 2026)

Accelerating carbon neutrality intensifies trade-offs in China’s energy-water-food nexus - Zhongshi Tang; Tao Wang; Sandylove Afrane; Nihed Benani; Yan Ru Fang; Pingjian Yang (Resources, Conservation and Recycling, 2026)

Identification and functional analysis of a double-stranded ribonuclease influencing RNAi efficiency in the striped flea beetle, Phyllotreta striolata - Mengli Chen; Keying Chen; Guoxing Chen; Peitong Chen; Dongping Chen; Jiali Qian; Guonian Zhu; Zhanyi Xu; Ru Yan (Pesticide Biochemistry and Physiology, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

A scaling-constrained symbolic intelligence approach for parameterizing submesoscale vertical heat transport - Bingzheng Yan; Junyi Wang; Ru Chen; Shan Huang; Tianmu Zheng; Kun Gao (Ocean Modelling, 2026)

Sugar profile in monofloral honeys from China: Implications for quality control - Ru Jia; Sha Yan; Xuezhe Huang; Zongyan Cui; Xiaofeng Xue (Food Chemistry, 2026)

Distinguishing the contributions of organic matter and iron (oxyhydr)oxides to zinc availability in paddy soils surrounding lead-zinc mines - Yecheng Li; Zebin Hong; Yan Ru; Guojun Chen; Xiaomin Li; Shiwen Hu; Yang Yang; Chao Guo; Shan Wang; Pengfei Cheng; Qi Wang; Tongxu Liu (Environmental Pollution, 2026)

Assessing synergy of CO2 and pollutant reductions in industrial parks from the industrial chain perspective - Shenghua Yan; Chen Cai; Jia Liu; Kaiming Peng; Ru Guo; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Slope aspect dominates over treeline position in structuring nitrogen-fixing microbial communities in Tibetan alpine ecotones - Jing-Ru Hao; Congcong Shen; Yan Li; Yuqiang Sang; Yuan Ge (Journal of Soils and Sediments, 2026)

Coronary CT Angiography-Based Prediction Model for Hemodynamically Significant Coronary Stenosis Integrating Morphological and Plaque Characteristics - Chenxi Wang; Shuang Leng; Ru-San Tan; Ping Chai; Jiang Ming Fam; Adrian Fatt Hoe Low; Lohendran Baskaran; Lynette Teo; Felix Yung Jih Keng; Chee Yang Chin; Ching Ching Ong; John C. Allen; et al. (Cardiovascular Engineering and Technology, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Comment on “On-site sanitation systems and fecal contamination in shallow groundwater in urban Indonesia: assessing influence of distance and rainfall variables” By G. L. Putri, A. M. Ilmi, R. Handayani, D. Iskandar, C. R. Priadi, J. Willetts, T. Foster; Water Research Volume 287 (Part B), 20 August 2025, 124431 - Huai-An Yin; Hin-San Paul Mak; Yan-Ru Xiao (Water Research, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Cyclopentanoid monoterpene glycosides from the aerial parts of Paederia foetida L - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Mechanism of adsorption and biodegradation of typical antibiotics by sediments in mariculture tailwater system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Zhi-Wei Zhou; Ze-Dong Lu; Xiao-Yan Fan (Environmental Research, 2026)

GaAs/GaN-based self-powered catalytic systems driven by tribovoltaic effect enable efficient degradation of azo dyes - Meng-Nan Liu; Yan-Xin Wu; Yu-Tong Sun; Xu Li; Ru Li; Jun Zhang; Yun-Ze Long (Chemical Engineering Journal, 2026)

Association between magnesium sulfate administration and mortality in critically ill patients with sepsis-associated acute kidney injury: a retrospective propensity score-matched cohort study - Xiang-Jie Duan; Jing-Ru Lan; Ming-Gao Zhu; Jin-Lian Chen; Chang-Yun Zhang; Hai-Yan Yin; Wan-Jie Gu (European Journal of Clinical Pharmacology, 2026)

Real-time visualization of Nocardia seriolae proliferation and macrophage migration in the Northern snakehead (Channa argus) - Jian Teng; Jian-Ru Liu; Yi-Xiang Zhai; Sheng-Liang Cao; Zhen-Shu Si; Qing-Teng Ren; Xiang-Shan Ji; Mei-Hua Lu; Yu-Bao Li; Yan Zhao (Aquaculture, 2026)

Construction of WO3/ZnIn2S4 Z-scheme heterojunction by electrostatic self-assembly to enhance charge separation and reactive oxygen species generation - Mengge Yan; Tingting Liu; Yushan Hu; Wenlong Bai; Mingfei Wei; Yuxuan Zhang; Xusheng He; Ru Li (Journal of Water Process Engineering, 2026)

Quantifying contributions of iron (oxyhydr)oxides and organic matter to chromium dynamics in paddy soils - Guojun Chen; Yang Yang; Ke Zhang; Yan Ru; Zebin Hong; Xiaomin Li; Taicheng An; Pei Wang; Songxiong Zhong; Qi Wang; Shiwen Hu; Fangbai Li; et al. (Geochimica et Cosmochimica Acta, 2026)

Transcriptional reprogramming and pathway engineering in Streptomyces lomondensis for efficient production of lomofungin - Ru-Xiang Deng; Ruo-Bing Yan; Wei Wang; Hong-Bo Hu; Xuehong Zhang (Chemical Engineering Journal, 2026)

Microbial functional shifts drive soil phosphorus transformation under long-term nitrogen and water inputs in a semi-arid grassland - Mohsin Mahmood; Ru Tian; Yan Shen; Jiatao Zhang; Lan Du; Anam Ayyoub; Ansa Rebi; Adnan Mustafa; Haoyue Chen; Yiming Zhao; Wenhuai Li; Le Qi; et al. (CATENA, 2026)

APMAP regulated by YY1 transcription mediates ferroptosis and metastasis in non-small cell lung cancer through the PI3K/AKT/mTOR pathway - Xiaohong Zhuang; Shu Lin; Cheng-sheng zhang; Qi Qin; Qixing Yan; Jing-ru Luo; Wenjun Tang (Journal of Molecular Histology, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Mechanistic link between eIF4E phosphorylation and viral pathogenesis: Therapeutic insights from a porcine model - Wen-Jun Tian; Yan-Ru Zhang; Jing-Ling You; Xiao-Jie Wu; Xiao-Fang Hu; Xiao-Jia Wang (Veterinary Microbiology, 2026)

Effects of nighttime warming and nitrogen addition on phytoplankton biomass in a submerged macrophytes-dominated freshwater wetland - Yaru Lyu; Jiayin Feng; Wenjing Ma; Chao Wang; Mengyu Yan; Zixuan Yang; Yunpeng Guo; Jinhua Zhang; Hongpeng Wang; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Journal of Environmental Sciences, 2026)

Sustainable extraction and bioconversion of tea stems using NADES: Dual benefits in polyphenolic recovery and carbohydrates enzymatic hydrolysis - Lin-Kun Sun; Pei-Ru Zhou; Tian Du; Yu-Cang Zhang; Yan-Zhen Zheng (Food Chemistry, 2026)

Effect of environmentally relevant concentrations of estrogens on the fear-like response of male zebrafish - Ying-Ying Zhang; Ru-Yi Tan; Hong Tao; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Built-in electric field and surface adsorption enhanced gas detection of muti-interface MXene/TiO2/Bi2MoO6 integrated heterostructure - Yan Liang; Peipei Yan; Xiaojian Zhao; Chunbo Ru; Lu Tang; Yu Jiang; Yong Yang (Chemical Engineering Journal, 2026)

Microglial Activation Mediates Drp1-Dependent Mitochondrial Fission and Neuronal Apoptosis in a Lipopolysaccharide-Induced Model of Cognitive Dysfunction - Meng-Jie Chen; Jia-Qi Ning; Jia-Xi Liu; Jian-Sheng Luo; Ru-Yu Yan; Yu-Xuan Yang; Xiang Li; Ling-Ling Ding (Molecular Neurobiology, 2026)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

A single Drosophila Dscam1 genomic locus generates a vast repertoire of circRNAs facilitated by RNA pairing - Zedong Li; Bingbing Xu; Zhechao Wang; Wenjie Zhang; Jiayan Fu; Lili Wu; Nengcheng Bao; Jinpeng Xie; Ru Yan; Haiyang Dong; Yongfeng Jin (Insect Biochemistry and Molecular Biology, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Nitrogen enrichment offsets the stimulation of soil respiration by increased precipitation in temperate grasslands - Ru Tian; Jiatao Zhang; Yan Shen; Lan Du; Jinbao Zhang; Shijia Yang; Zhongxiang Liu; Mengle Wang; Zhuwen Xu (Agricultural and Forest Meteorology, 2025)

Ionic liquids accelerate the crystallization of a magnetic fluorine-functionalized 3D covalent organic framework for efficient capture of trace benzoylurea insecticides in juices and beverages - Zekun Liu; Lu Liu; Yan Dong; Yan Li; Chong Zhang; Xiao-Li Wang; Lingxi Zhao; Hai-Long Jiang; Yong-Ning Wu; Xiangfeng Chen; Feng Li; Ru-Song Zhao (Chemical Engineering Journal, 2025)

Enrichment of Feammox microflora utilizing in-situ iron in excess activated sludge: substrate metabolism, gene variation, and microbial communities - Maoxia Chen; Jing Ru; Yan Yi; Yang Li; Liang Wu; Huiling Jiang (Bioresource Technology, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

The new ten-numbered macrolide, diaporthsin L, from endophytic fungus Diaporthe sp. G-4 isolated from Strobilanthes cusia (Nees) Kuntze - Jun-yi Li; Zhen-xian Cun; Hui-hui Sun; Jie-Zheng Shi; Wen-xiang Yan; Jun-meng Xia; Dong Gan; Mao-ru Li; Ju-cheng Zhang; Zhong-tao Ding (Natural Product Research, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Corrigendum to “Characterization of γ-CD-MOF-stabilized thymol pickering emulsion films with enhanced preservation properties for Basa (Pangasius) fish” [Food Chemistry 476 (2025) 143273] - Yiyi Cheng; Xiaoguo Ying; Xuemei Cai; Yin Chen; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2025)

Covalent binding of vitamin K3 photosensitizers to nanofibrous membranes for daylight-driven antimicrobial applications - Yibo Ru; Qingli Dong; Kexin Li; Xinyi Zhao; Lang Yan; Xiang Wang; Yangtai Liu; Yue Ma (Chemical Engineering Journal, 2025)

Design of 2D/2D Pt SA-MoS2/ZnIn2S4 photocatalysts for boosting hydrogen production - Xue-Lu Chen; Miao Ni; Yan-Ru Li; Yi-An Pan; Chen Chi; Yi Yang; Si-Meng Li; Sudip Biswas; Yi-Bai Sun; Xing-Hua Xia (Chemical Engineering Journal, 2025)

Construction and optimization of low carbon-to-nitrogen ratio-adapted Chlorococcum-Bacteria symbiosis for energy-efficient wastewater remediation - Ru Yan; Han Ji; Zhuo-Chao Liu; Mei-Qi Ren; Shuai Wang; Li-Ming Yang; Dan Cui (Bioresource Technology, 2025)

Anaerobic Digestion Enhances the Comprehensive Utilization of Shaddock Peel: Methane Production, Biochar Preparation, and CO2 Capture - Chengcheng Cao; Ru Li; Huantao Dai; Yan Zhao; Ling Sun; Xinheng Zhuang; Xueyang Zhang (Water, Air, & Soil Pollution, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Orchard variable rate spraying method and experimental study based on multidimensional prescription maps - Chenming Hu; Yu Ru; Shuping Fang; Zifan Rong; Hongping Zhou; Xianghai Yan; Mengnan Liu (Computers and Electronics in Agriculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Flavonoids and butanolides from the bark of Machilus robusta and their bioactivities - Rui-Qi Liu; Shan-Shan Ling; Xian-Da Hu; Bing Peng; Yan-Ru Li (Phytochemistry Letters, 2025)

The heading stage: A critical period for schwertmannite in reducing arsenic accumulation in rice (Oryza sativa L.) - Yan Dong; Jiawei Yang; Ru Wang; Bo Zhou; Mingjiang Zhang; Guanyu Zheng; Lixiang Zhou (Journal of Environmental Sciences, 2025)

Factors affecting seed germination in critically endangered Salvia daiguii: Seed quality, temperature and light, osmotic potential, pH, hand pollination, hormones, and mucilage - Han-Wen Xiao; Ruo-Qing Jiang; Yan-Bo Huang; Ru-Nan Tian (Journal for Nature Conservation, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Atmospheric microplastic deposition in Guilin karst wetlands: Sources and agricultural impact - Lishan Zhang; Bihong Xu; Zengxian Wei; Xiaolu Liang; Yan Chen; Xuan Ru; Qian Zhang; Shan Zhong (Atmospheric Pollution Research, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Different responses of phytoplankton taxa to water N and P inputs in a freshwater wetland: A mesocosm study - Wenjing Ma; Jiayin Feng; Jinhua Zhang; Hongpeng Wang; Yunpeng Guo; Yaru Lyu; Chao Wang; Zixuan Yang; Mengyu Yan; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Marine Pollution Bulletin, 2025)

Isolation and identification of triterpenoid saponins with antiproliferative and hemolytic activities from Camellia oleifera Abel seeds - Jian-Fa Zong; Xiao-Xiang Guo; Kang-Kang Zou; Chuan-Jian Cui; Zi-Hui Hu; Ru-Yan Hou (Phytochemistry, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Characterization of γ-CD-MOF-stabilized thymol Pickering emulsion films with enhanced preservation properties for Basa (Pangasius) fish - Yiyi Cheng; Xiaoguo Ying; Xuemei Cai; Yin Chen; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2025)

Functional analysis of Ophraella communa Lesage OcomOBP11 in recognition of Ambrosia artemisiifolia L. volatiles - Yang Yue; Chao Ma; Yan Zhang; Wei-hua Ma; Jing-jing Wang; Zhen-ya Tian; Guang-mei Chen; Ru-wen Li; Jin-hua Li; Jing-fang Yang; Zhong-shi Zhou (Pesticide Biochemistry and Physiology, 2025)

Impact of typhoon on nutrient contaminants, antibiotic resistance genes and microbial communities in mariculture tailwater treatment system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Xiao-Yan Fan (Environmental Research, 2025)

Energy storage in Hf0.5Zr0.5O2(3):ZrO2(12)-based films with heterostructures formed at different deposition temperatures - Haiyan Chen; Chengfeng Jiang; Lei Liu; Ru Guo; Zhongna Yan; Chuanchang Li; Dou Zhang (Chemical Engineering Journal, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Metagenomics and metatranscriptomics uncover the regulatory mechanism of nitrogen metabolism response to aggregation status of anammox bacteria - Ru Wang; Jinshi Lian; Wenyan Wang; James P. Shapleigh; Longxing Jiang; Yahui Wang; Yan Huang; Ling Xie; Liangwei Deng; Wenguo Wang; Lan Wang (Chemical Engineering Journal, 2025)

Synthesis of hollow HC-Ni0.96S@MXene/C nanobox as advanced anode for lithium-ion and sodium-ion battery - Song-Yi Liao; Jing Chen; Dao-Ren Deng; Cai-Yun Wu; Selina X. Yao; Yi Wang; Yu-Ming Ru; Xiao-Yan Li; Xu-Gang Shu; Yong-Gang Min (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Designing multilayer interlocked architectures with vertical LDH nanosheets in ZIF-67 composite membranes for upgrading CO2 separation - Yan-Mei Zhang; Li-Hao Xu; Xiao-Xue Hu; Bing-Hong Chen; Xin-Ru Chen; Qian-Qian Li; Heng Mao; Zhi-Ping Zhao (Chemical Engineering Journal, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Sediment Provenance and Facies Analysis of the Huagang Formation in the Y-Area of the Central Anticlinal Zone, Xihu Sag, East China Sea - Xiao Ma; Wei Yan; Yi Yang; Ru Sun; Yue Chao; Guoqing Zhang; Chao Yang; Shudi Zhang; Dapeng Su; Guangxue Zhang; Hong Xu (Journal of Marine Science and Engineering, 2025)
Recent breakthrough exploration wells in the Huagang Formation in the Y-area of the central anticlinal zone of the Xihu Sag have confirmed the significant exploration potential of structure–lithology complex hydrocarbon reservoirs. However, limited understanding of the provenance system, sedimentary facies, and microfacies has hindered further progress in complex hydrocarbon exploration. Analysis of high-precision stratigraphic sequences and seismic facies data, mudstone core color, grain-size probability cumulative curves, core facies, well logging facies, lithic type, the heavy-mineral ZTR index, and conglomerate combinations in drilling sands reveals characteristics of the source sink system and provenance direction. The Huagang Formation in the Y-area represents an overall continental fluvial delta sedimentary system that evolved from a braided river delta front deposit into a meandering river channel large-scale river deposit. The results indicate that the primary provenance of the Huagang Formation in the Y-area of the Xihu Sag is the long-axis provenance of the Hupi Reef bulge in the northeast, with supplementary input from the short-axis provenance of the western reef bulge. Geochemical analysis of wells F1, F3, and G in the study area suggests that the prevailing sedimentary environment during the period under investigation was characterized by anoxic conditions in nearshore shallow waters. This confirms previous research indicating strong tectonic reversal in the northeast and a small thickness of the central sand body unrelated to the flank slope provenance system. The aforementioned findings deviate from conventional understanding and will serve as a valuable point of reference for future breakthroughs in exploration.

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Knockdown and insecticidal activities of pyrethrum, dimefluthrin and meperfluthrin against Aedes aegypti and Aedes albopictus - Mengli Chen; Ru Yan; Zhanyi Xu; Qiaoling Zhou; Yuyan Wu (International Journal of Tropical Insect Science, 2025)

Two new phenolic glycosides from the rhizomes of Paris yunnanensis - Yu-Rui Xie; Shan-Shan Ling; Yan-Xi Li; Mei-Ru Wang; Hai-Yang Liu (Phytochemistry Letters, 2025)

Insights into the source characterization, risk assessment and ozone formation sensitivity of ambient VOCs at an urban site in the Fenwei Plain, China - Huan Zhang; Chen Zhang; Shasha Liu; Shijie Yin; Siqing Zhang; Hongji Zhu; Fengyu Yan; Hua Yang; Xiaoning Ru; Xingang Liu (Journal of Hazardous Materials, 2025)

Impact of carbon/nitrogen ratio on sequencing batch biofilm reactors initiated with different seed sludges for treating actual mariculture effluents - Xiao-Yan Fan; Shi-Long Zhou; Yanling Yang; Shen-Bin Cao; Yue Niu; Meng-Yuan Zheng; Jun-Ru Zhao (Bioresource Technology, 2025)

Rapid and visual detection of the strawberries pathogenic fungi Fusarium oxysporum and Colletotrichum siamense by one-pot LAMP-CRISPR/Cas12b - Ya-Ru Tian; Dong-Lan Tang; Tian-Qi Wang; Jia-Yue Chen; Yan-Fang Dong; Xin-Yu Ying; Dan Zhang; Wen-Jing Wang; Zhi-Dan Luo (Journal of Plant Diseases and Protection, 2025)

Evaluation on the antibacterial activity of glycyrrhizin against Pseudomonas plecoglossicida in ayu fish (Plecoglossus altivelis) - Fan Tao; Jia-Feng Cao; Yan-Jun Liu; Ru-Yi Chen; Jin-Jin Shi; Chang-Yun Li; Jian-Fei Lu; Guan-Jun Yang; Jiong Chen (Aquaculture, 2025)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Integrative models for environmental forecasting of phthalate migration from microplastics in aquaculture environments - Shan Zhong; Ruiyue Li; Yaowen Tian; Zengxian Wei; Lishan Zhang; Yan Chen; Ruyue Zhou; Qian Zhang; Xuan Ru (Journal of Hazardous Materials, 2024)

Mechanistic insights into the efficient activation of peracetic acid by mackinawite (FeS) for diclofenac degradation under near-neutral conditions: Multiple identification and contribution of non-radicals - Yao-Feng Gao; Yan-Ping Duan; Yu-Ru Chen; Yuan-Hua Jia; Yao-Jen Tu; Chao-Meng Dai (Chemical Engineering Journal, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

A review of urinary HPV testing for cervical cancer management and HPV vaccine surveillance: rationale, strategies, and limitations - Lin Cheng; Ru Wang; Jing Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Nitrogen addition alleviates the negative effects of reduction in precipitation on soil multifunctionality in a typical steppe - Yan Shen; Yonghong Luo; Lan Du; Ru Tian; Wenqian Shao; Jiatao Zhang; Na Li; Jinbao Zhang; Shan Wang; Mohsin Mahmood; Zhuwen Xu (Applied Soil Ecology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Harnessing the plant microbiome for environmental sustainability: From ecological foundations to novel applications - Jing-Ru Hao; Yan Li; Yuan Ge (Science of The Total Environment, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Dissect the association between per- and polyfluoroalkyl substances (PFAS) and kidney function from the perspective of lipid molecules - Yi-Ran Chen; Shao-Bin Lin; Jia-Yun Lv; Yan Wu; Wen-Ru Feng (Environmental Pollution, 2024)

Nickel sulfide nanorods encapsulated in Nitrogen-Doped carbon on nickel foam in situ derived from Saccharomycetes cerevisiae for the selective oxidation of biomass - Hao Chen; Si-Ru Chen; Qing Yang; Le-Xing You; Qun-Feng Ye; Ai-Jun Wang; Dong-Hai Lin; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Dually-amplified electrochemical aptasensor based on the self-linking AuPt nanoflowers for ultrasensitive determination of hemagglutinin - Qing-Cai Yu; Yan Wang; Yao Liu; Chan-Ru Xiong; Xing Chen (Analytica Chimica Acta, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

Metabolic pathways altered by air pollutant exposure in association with coagulation function among the rural elderly - Haoyu Huang; Ru-Qing Liu; Yan Chen; Yuewei Liu; Guang-Hui Dong; Jian Hou; Shanshan Li; Yuming Guo; Chongjian Wang; Gongbo Chen (Journal of Hazardous Materials, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Diaper-based wearable SERS sensing system with a silver nano dual-structure composite hydrogel for the detection of biomarkers and pH in urine - Ru Liu; Qingling Nie; Yanhanzhuo Wang; Yan Wu; Yeting Tu; Chunling Xie; Xiufeng Xiao; Ruiyun You; Yudong Lu (Chemical Engineering Journal, 2024)

Sodium Selenite Ameliorates Silver Nanoparticles Induced Vascular Endothelial Cytotoxic Injury by Antioxidative Properties and Suppressing Inflammation Through Activating the Nrf2 Signaling Pathway - Yunyun Ma; Lei Wang; Jing He; Xueping Ma; Jingjing Wang; Ru Yan; Wanrui Ma; Huiyan Ma; Yajuan Liu; Hongqian Sun; Xiaoxia Zhang; Shaobin Jia; et al. (Biological Trace Element Research, 2024)
Silver nanoparticles (AgNP) are the dominant nanomaterials in commercial products and the medical field, but the widespread occurrence of AgNP has become a global threat to human health. Growing studies indicate that AgNP exposure can induce vascular endothelial toxicity by excessive oxidative stress and inflammation, which is closely related to cardiovascular disease (CVD), but the potential intrinsic mechanism remains poorly elucidated. Thus, it has been crucial to control the toxicological effects of AgNP in order to improve their safety and increase the outcome of their applications. Multiple researches have demonstrated that sodium selenite (Se) possesses the capability to counteract the toxicity of AgNP, but the functional role of Se in AgNP-induced CVD is largely unexplored. The aim of this study was to explore the potential protective effect of Se on AgNP-induced vascular endothelial lesion and elucidate the underlying mechanisms. An in vivo model of toxicity in animals was established by the instillation of 200 µL of AgNP into the trachea of rats both with (0.2 mg/kg/day) and without Se treated. In vitro experiments, human umbilical vein endothelial cells (HUVECs) were incubated with AgNP (0.3 µg/mL ) and Se for a duration of 24 h. Utilizing transmission electron microscopy, we observed that the internalization of AgNP-induced endothelial cells was desquamated from the internal elastic lamina, the endoplasmic reticulum was dilated, and the medullary vesicle formed. Se treatment reduced the levels of vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1), inhibited the release of pro-inflammatory cytokines (specifically tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6), improved endothelial cell permeability, integrity, and dysfunction, and prevented damage to the aortic endothelium caused by AgNP. Importantly, we found that Se showed the capacity against AgNP with biological functions in guiding the intracellular reactive oxygen species (ROS) scavenging and meanwhile exhibiting anti-inflammation effects. Se supplementation decreased the intracellular ROS release and suppressed NOD-like receptor protein 3 (NLRP3) and nuclear factor kappa-B (NF-κB) mediated inflammation within AgNP-intoxicated rats and HUVECs. The anti-oxidant stress and anti-inflammatory effects of Se were at least partly dependent on nuclear factor erythroid 2-related factor 2 (Nrf2). Overall, our results indicated that the protectiveness of Se against AgNP-induced vascular endothelial toxicity injury was at least attributed to the inhibition of oxidative ROS and pro-inflammatory NF-κB/NLRP3 inflammasome by activating the Nrf2 and antioxidant enzyme (HO-1) signal pathway.

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Drought and nitrogen deposition regulate plant nutrient resorption in a typical steppe - Yonghong Luo; Yan Shen; Ahmed Salah Elrys; Lan Du; Mohsin Mahmood; Jiatao Zhang; Haiyan Ren; Jinbao Zhang; Na Li; Ru Tian; Wenqian Shao; Ahmed S.M. Elnahal; et al. (Agriculture, Ecosystems & Environment, 2024)

Applications in Pickering emulsions of enhancing preservation properties: Current trends and future prospects in active food packaging coatings and films - Yiyi Cheng; Xuemei Cai; Xin Zhang; Yadong Zhao; Ru Song; Yan Xu; Haiyan Gao (Trends in Food Science & Technology, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Glycine to valine substitution in the short intracellular linkers of domain II enhances I1011M-mediated sodium channel resistance to Type I pyrethroids, but not Type II pyrethroids - Mengli Chen; Xiangyi Zhou; Guoxing Chen; Zhanyi Xu; Jiali Qian; Guonian Zhu; Ru Yan (Pesticide Biochemistry and Physiology, 2024)

Study on factors influencing carbon dioxide emissions and carbon peak heterogenous pathways in Chinese provinces - Runpu Liu; Yan Ru Fang; Shuan Peng; Nihed Benani; Xuefang Wu; Yushuo Chen; Tao Wang; Qimin Chai; Pingjian Yang (Journal of Environmental Management, 2024)

Effect of heating treatment on processing characteristics of rice dough - Wan-ru Liu; Chun-min Ma; Yang Yang; Bing Wang; Xiao-fei Liu; Yan Wang; Xin Bian; Xiao-xue Guo; Guang Zhang; Na Zhang (Innovative Food Science & Emerging Technologies, 2024)

LECT2 mediates antibacterial immune response induced by Nocardia seriolae infection in the northern snakehead - Jian Teng; Yan Zhao; Yu Bao Li; Liang Yi Xue; Yi Xiang Zhai; Jian Ru Liu; Hui Wang; Xiang Shan Ji (Fish & Shellfish Immunology, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Screening of Strain from Reconstituted Sheet Tobacco Making High-Yield Enzyme and Aroma - Chun-Xue Yang; Deng Zhang; Hui Ma; Xiao-Meng Guo; Na Yan; Xue-Ting Deng; Xiang-Ru Liao; Zheng-Bing Guan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Reduction in precipitation amount, precipitation events, and nitrogen addition change ecosystem carbon fluxes differently in a semi-arid grassland - Lan Du; Yonghong Luo; Jiatao Zhang; Yan Shen; Jinbao Zhang; Ru Tian; Wenqian Shao; Zhuwen Xu (Science of The Total Environment, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

Unraveling the effect of combined heat and high-pressure homogenization treatment on the improvement of chickpea protein solubility from the perspectives of colloidal state change and structural characteristic modification - Yu Wang; Jing-jing Yuan; Ya-ru Zhang; Xing Chen; Jia-le Wang; Bo Chen; Ke Li; Yan-hong Bai (Food Chemistry, 2024)

A macromolecular Gleditsia Saponin induces apoptosis of leukemia cells through Fas-mediated death receptor pathway and mitochondrial pathway - Wen-jie Ding; Yao Huo; Zhen-tong Li; Yan-ru Liu; Ke-yao Dai; Chao Liu; Hai-yu Ji; An-jun Liu (Food Bioscience, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Dissolved oxygen and ammonia affect ammonia production via GDH/AMPK signaling pathway and alter flesh quality in Chinese perch (Siniperca chuatsi) - Ru Yang; Xuange Liu; Yong Liu; Qingda Tian; Ziwei Wang; Dejie Zhu; Zhisong Qian; Yi Yi; Jiacheng Hu; Yan Li; Xu-Fang Liang; Liwei Liu; et al. (Fish Physiology and Biochemistry, 2024)

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Pivotal role of intracellular oxidation by HOCl in simultaneously removing antibiotic resistance genes and enhancing dewaterability during conditioning of sewage sludge using Fe2+/Ca(ClO)2 - Xinxin Wang; Yu Lu; Yiwen Yan; Ru Wang; Yuhang Wang; Hua Li; Lixiang Zhou; Guanyu Zheng; Yifeng Zhang (Water Research, 2024)

Assessing climate/air quality synergies and cost-effectiveness for Beijing transportation: Insights into sustainable development - Xuefang Wu; Roy M. Harrison; Min Chen; Tao Wang; Ruihe Lyu; Shuan Peng; Runpu Liu; Yushuo Chen; Yan Ru Fang; Pingjian Yang (Sustainable Cities and Society, 2024)

High-Performance enrichment and sensitive analysis of bisphenol and its analogues in water and milk using a novel Ni-Based cationic Metal-Organic framework - Jin-Yan Ma; Hai-Long Jiang; Fu-Shuai Kang; Lu Liu; Xia Wang; Ru-Song Zhao (Food Chemistry, 2024)

Efficient removal of size-fractionated antibiotic resistance genes (ARGs) in WWTPs secondary effluent by vacuum ultraviolet (VUV) activated potassium peroxymonosulfate (PMS) - Xiao-Yan Fan; Shi-Long Xu; Xing Li; Zhi-Wei Zhou; Yu-Xi Gao; Jun-Ru Zhao; Zhong-Xing Zhang (Chemical Engineering Journal, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

The NADase CD38 is a central regulator in gouty inflammation and a novel druggable therapeutic target - Paulo Gil Alabarse; Patricia Oliveira; Huaping Qin; Tiffany Yan; Marie Migaud; Robert Terkeltaub; Ru Liu-Bryan (Inflammation Research, 2024)
Objectives Cellular NAD + declines in inflammatory states associated with increased activity of the leukocyte-expressed NADase CD38. In this study, we tested the potential role of therapeutically targeting CD38 and NAD + in gout. Methods We studied cultured mouse wild type and CD38 knockout (KO) murine bone marrow derived macrophages (BMDMs) stimulated by monosodium urate (MSU) crystals and used the air pouch gouty inflammation model. Results MSU crystals induced CD38 in BMDMs in vitro, associated with NAD + depletion, and IL-1β and CXCL1 release, effects reversed by pharmacologic CD38 inhibitors (apigenin, 78c). Mouse air pouch inflammatory responses to MSU crystals were blunted by CD38 KO and apigenin. Pharmacologic CD38 inhibition suppressed MSU crystal-induced NLRP3 inflammasome activation and increased anti-inflammatory SIRT3–SOD2 activity in macrophages. BMDM RNA-seq analysis of differentially expressed genes (DEGs) revealed CD38 to control multiple MSU crystal-modulated inflammation pathways. Top DEGs included the circadian rhythm modulator GRP176 , and the metalloreductase STEAP4 that mediates iron homeostasis, and promotes oxidative stress and NF-κB activation when it is overexpressed. Conclusions CD38 and NAD + depletion are druggable targets controlling the MSU crystal- induced inflammation program. Targeting CD38 and NAD + are potentially novel selective molecular approaches to limit gouty arthritis.

Prediction of cytochrome P450-mediated bioactivation using machine learning models and in vitro validation - Xin-Man Hu; Yan-Yao Hou; Xin-Ru Teng; Yong Liu; Yu Li; Wei Li; Yan Li; Chun-Zhi Ai (Archives of Toxicology, 2024)

Experiments and CFD simulation of downwash airflow and fog distribution discharged from a single-rotor UAV fitted with a pulse-jet thermal fogging machine - Jian Zhang; Qing Chen; Jian Liu; Yan Wang; Hongping Zhou; Fengbo Yang; Yu Ru (Biosystems Engineering, 2024)

Arabidopsis HAPLESS13/AP-1µ is critical for pollen sac formation and tapetal function - Gui-Min Yin; Yi-Ru Fang; Jia-Gang Wang; Yue Liu; Xiaojiao Xiang; Sha Li; Yan Zhang (Plant Science, 2024)

Enhancing phenology modeling through the integration of artificial light at night effects - Haoming Xia; Longxin Qiao; Yan Guo; Xutong Ru; Yaochen Qin; Yuyu Zhou; Chaoyang Wu (Remote Sensing of Environment, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

6PPD-quinone exposure induces neuronal mitochondrial dysfunction to exacerbate Lewy neurites formation induced by α-synuclein preformed fibrils seeding - Jiacheng Fang; Xiaoxiao Wang; Guodong Cao; Fuyue Wang; Yi Ru; Bolun Wang; Yanhao Zhang; Doudou Zhang; Jie Yan; Ji Xu; Jing Ji; Fenfen Ji; et al. (Journal of Hazardous Materials, 2024)

Comprehensive evaluation of antibiotics pollution the Yangtze River basin, China: Emission, multimedia fate and risk assessment - Yu-Ru Chen; Yan-Ping Duan; Zhi-Bo Zhang; Yao-Feng Gao; Chao-Meng Dai; Yao-Jen Tu; Jun Gao (Journal of Hazardous Materials, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Exposures to drinking water disinfection byproducts and kidney function in Chinese women - Cheng-Ru Li; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Chong Liu; Qiang Zeng (Environmental Research, 2024)

Characterization of CM-Dil-labeled Muse cells in culture and in skin wounds in rats - Yan-yun Cao; Jing Ning; Ru-zhi Zhang; Kang Ge; Ting-ting Huang (Cell and Tissue Banking, 2024)

Biological upcycling of nickel and sulfate as electrocatalyst from electroplating wastewater - Xian-Zhong Fu; Yu-Ru Yang; Tian Liu; Zhi-Yan Guo; Chen-Xuan Li; Hai-Yang Li; Kang-Ping Cui; Wen-Wei Li (Water Research, 2024)

Silver nanoparticles induce endothelial cytotoxicity through ROS-mediated mitochondria-lysosome damage and autophagy perturbation: The protective role of N-acetylcysteine - Jing He; Yunyun Ma; Xudong Niu; Jiansheng Pei; Ru Yan; Fangjing Xu; Jing Ma; Xiaojuan Ma; Shaobin Jia; Wanrui Ma (Toxicology, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Does biogas industrial policy promote the industrial transformation? - Erga Luo; Ru Yan; Yaping He; Zhen Han; Yiyu Feng; Wenrong Qian; Jinkai Li (Resources Policy, 2024)

Accelerated removal of naproxen in the iron-based peracetic acid activation system by chloride ions: Enhancement of reactive oxidative species via the formation of iron-chloride complexes - Si-Ying Yu; Yang Shi; Chuan-Shu He; Yu-Dan Dong; Si Sun; Ru-Yan Ning; Zhao-Kun Xiong; Peng Zhou; Heng Zhang; Bo Lai (Journal of Hazardous Materials, 2024)

Associations between urinary biomarkers of exposure to disinfection byproducts and semen parameters: A repeated measures analysis - Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Chong Liu; Jia-Yue Zeng; Yu Miao; Yang Wu; Cheng-Ru Li; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Qiang Zeng (Journal of Hazardous Materials, 2024)

Comammox plays a functionally important role in the nitrification of rice paddy soil with different nitrogen fertilization levels - Kai Zhang; Hui-Feng Sun; You-Cai Kang; Ran Jiang; Yan-Ren Wang; Ru-Yi Zhang; Sheng-Nan Zhang; Yang-Yang Li; Peng Li; Fan Yang; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2024)

Genome resources for the elite bread wheat cultivar Aikang 58 and mining of elite homeologous haplotypes for accelerating wheat improvement - Jizeng Jia; Guangyao Zhao; Danping Li; Kai Wang; Chuizheng Kong; Pingchuan Deng; Xueqing Yan; Xueyong Zhang; Zefu Lu; Shujuan Xu; Yuannian Jiao; Kang Chong; et al. (Molecular Plant, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Mitogenome analysis reveals predominantly ancient Yellow River origin of population inhabiting Datong agro-pastoral ecotone along Great Wall - Yuqing Yan; Panxin Du; Jihong Zhang; Ruilan Li; Haoquan Bao; Qingli Fang; Ye Gao; Hailiang Meng; Yiran Xu; Haochen Shi; Hailong Yan; Xin Chang; et al. (Molecular Genetics and Genomics, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Advances in understanding entire process of medium chain carboxylic acid production from organic wastes via chain elongation - Qingyan Wang; Nan Yang; Yajing Cai; Ru Zhang; Yan Wu; Weifang Ma; Chuan Fu; Panyue Zhang; Guangming Zhang (Chemosphere, 2023)

Thermodynamic analysis of the biomass gasification Allam cycle - Yidan Fu; Lei Cai; Ru Yan; Yanwen Guan (Fuel, 2023)

Exploration of using acoustic vibration technology to non-destructively detect moldy kernels of in-shell hickory nuts (Carya cathayensis Sarg.) - Qing-li Han; Bai-xue Long; Xue-jun Yan; Wu Wang; Feng-ru Liu; Xue Chen; Fei Ma (Computers and Electronics in Agriculture, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Effects of combined antibiotics on nitrification, bacteria and antibiotic resistance genes in activated sludge: Insights from legacy effect of antibiotics - Zhong-Xing Zhang; Xiao-Yan Fan; Xing Li; Yu-Xi Gao; Jun-Ru Zhao (Journal of Environmental Sciences, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Leucine to tryptophane substitution in the pore helix IIP1 confer sodium channel resistance to pyrethroids and DDT - Huiming Wu; Jiali Qian; Zhanyi Xu; Ru Yan; Guonian Zhu; Shaoying Wu; Mengli Chen (Pesticide Biochemistry and Physiology, 2023)

Aerobic granulation in an oxidation ditch using the residual sludge after extracting slime-extracellular polymer substances - Yan-Ru Jia; Zheng-Hong Wen; Yi-Jiang Shang-Guan; Zhi-Hua Li (Journal of Water Process Engineering, 2023)

Understanding the digestibility of wheat starch- caffeic acid complexes prepared by hot-extrusion 3D printing technology - Xin-Ru Cui; Yu-Sheng Wang; Yan Chen; Hong-Yan Mu; Hai-Hua Chen (Food Hydrocolloids, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Inhibitory effect of Portulaca oleracea L. aqueous extract and juice on NLRP3 inflammasome activation in an ulcerative colitis mouse model - Yi-meng Fan; Yuan-yuan Wei; Hui-ru Wang; Yu-Ga; Yan-nan Zhang; Zhihui Hao (Environmental Science and Pollution Research, 2023)

Gestational 1-nitropyrene exposure causes anxiety-like behavior partially by altering hippocampal epigenetic reprogramming of synaptic plasticity in male adult offspring - Bo Wang; Ting Zhao; Xiao-Xi Chen; Yan-Yan Zhu; Xue Lu; Qing-Hua Qian; Hui-Ru Chen; Xiu-Hong Meng; Hua Wang; Wei Wei; De-Xiang Xu (Journal of Hazardous Materials, 2023)

Research on fuzzy weighted gain scheduling water level control system of U-tube steam generator - Leilei Qiu; Yan Huo; Ru Zhang; Haomin Wang; Guanfu Jiang; Peiwei Sun; Xinyu Wei (Annals of Nuclear Energy, 2023)

Volatile fatty acid production in anaerobic fermentation of food waste saccharified residue: Effect of substrate concentration - Qingyan Wang; Guangming Zhang; Le Chen; Nan Yang; Yan Wu; Wei Fang; Ru Zhang; Xinyi Wang; Chuan Fu; Panyue Zhang (Waste Management, 2023)

Soil erosion effectively alleviated by Miscanthus sacchariflorus, a potential candidate for land deterioration improvement - Chu Zhao; Yu-han Nie; Jian-pan Xin; Xiao-yu Zhu; Yan Li; Ru-nan Tian (Rhizosphere, 2023)

Effects of microbial transglutaminase on the gelling property and in vitro digestibility of fish scale gelatin from grass carp - Yonggang Chen; Yuhang Wang; Ru Liu; Shanbai Xiong; Yan Xu; Yang Hu (Food Bioscience, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

4-OI ameliorates bleomycin-induced pulmonary fibrosis by activating Nrf2 and suppressing macrophage-mediated epithelial-mesenchymal transition - Ya-xian Wu; Ya-ru Zhang; Feng-juan Jiang; Shuai He; Yan-li Zhang; Dan Chen; Ying Tong; Yun-juan Nie; Qing-feng Pang (Inflammation Research, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Valorization of soybean pulp for sustainable α-ketoisocaproate production using engineered Bacillus subtilis whole-cell biocatalyst - Eugene Huang; Jhen-Sheng Yan; Ronnie G. Gicana; Yin-Ru Chiang; Fang-I Yeh; Chieh-Chen Huang; Po-Hsiang Wang (Chemosphere, 2023)

Renewable pickering emulsion system based on bifunctional materials for highly efficient fuel oil desulfurization without stirring - Shuai-Yong Dou; Jia-Yu An; Yan-Ru Feng; Kang Liu; Xuan Wang; Bo-Wen Zhang; Jing-Xuan Zhang; Er-Hong Duan; Ai-Bin Kang (Fuel, 2023)

Atmospheric solids analysis probe-mass spectrometry (ASAP-MS) as a rapid fingerprinting technique to differentiate the harvest seasons of Tieguanyin oolong teas - Hui Ru Tan; Li Yan Chan; Adabelle Ong; Yong-Quan Xu; Xue-Bo Zhang; Weibiao Zhou (Food Chemistry, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Methylated Chromenoquinoline as a Novel Nucleus Fluorescent Probe for Nucleic Acid Imaging - Zhi-Hao Zhang; Qing Yu; Gang Zhang; Hai-Yan Peng; Ru Sun; Yu-Jie Xu; Jian-Feng Ge (Journal of Fluorescence, 2023)

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

Prodigiosin as an antibiofilm agent against multidrug-resistant Staphylococcus aureus - Jing Yan; Qi Yin; Hao Nie; Jinyou Liang; Xiang-Ru Liu; Yingli Li; Hong Xiao (Biofouling, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Genomic vulnerability to climate change in Quercus acutissima , a dominant tree species in East Asian deciduous forests - Shuai Yuan; Yong Shi; Biao‐Feng Zhou; Yi‐Ye Liang; Xue‐Yan Chen; Qing‐Qing An; Yan‐Ru Fan; Zhao Shen; Pär K. Ingvarsson; Baosheng Wang (Molecular Ecology, 2023)
Understanding the evolutionary processes that shape the landscape of genetic variation and influence the response of species to future climate change is critical for biodiversity conservation. Here, we sampled 27 populations across the distribution range of a dominant forest tree, Quercus acutissima , in East Asia, and applied genome‐wide analyses to track the evolutionary history and predict the fate of populations under future climate. We found two genetic groups (East and West) in Q. acutissima that diverged during Pliocene. We also found a heterogeneous landscape of genomic variation in this species, which may have been shaped by population demography and linked selections. Using genotype‐environment association analyses, we identified climate‐associated SNPs in a diverse set of genes and functional categories, indicating a model of polygenic adaptation in Q. acutissima . We further estimated three genetic offset metrics to quantify genomic vulnerability of this species to climate change due to the complex interplay between local adaptation and migration. We found that marginal populations are under higher risk of local extinction because of future climate change, and may not be able to track suitable habitats to maintain the gene–environment relationships observed under the current climate. We also detected higher reverse genetic offsets in northern China, indicating that genetic variation currently present in the whole range of Q. acutissima may not adapt to future climate conditions in this area. Overall, this study illustrates how evolutionary processes have shaped the landscape of genomic variation, and provides a comprehensive genome‐wide view of climate maladaptation in Q. acutissima .

Toward sustainable utilization of crop straw: Greenhouse gas emissions and their reduction potential from 1950 to 2021 in China - Wenjun Shi; Yan Ru Fang; Yuyang Chang; Guang Hui Xie (Resources, Conservation and Recycling, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Effects of H2O2 acclimation on the growth, polysaccharide production and tolerance performance of Nostoc flagelliforme - Shu-ting Liu; Shuai Wang; Na Han; Meng-yuan Li; Jian Li; Yan-ru Li; Shi-ru Jia; Pei-pei Han (Algal Research, 2023)

Genomic analysis of Marinimicrobium sp. C6131 reveals its genetic potential involved in chitin metabolism - Yan-Ru Dang; Xiao-Yu Zhang; Sha-Sha Liu; Ping-Yi Li; Xue-Bing Ren; Qi-Long Qin (Marine Genomics, 2023)

Response of activated sludge to antibiotics stress: Neglected legacy effects - Zhong-Xing Zhang; Xiao-Yan Fan; Xing Li; Yu-Xi Gao; Jun-Ru Zhao (Journal of Water Process Engineering, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Performance optimizing and entropy generation analysis of a platinum–stainless-steel segmented microreactor - Yueh-Heng Li; Hsiao-Hsuan Kao; Yan-Ru Wang; Jianlong Wan; Kanit Manatura (Chemical Engineering Journal, 2023)

Treatment of heavy metal ions-polluted water into drinkable water: Capture and recovery of Pb2+ by cellulose@CaCO3 bio-composite filter via spatial confinement effect - He-Xiang Zhao; Yan Wang; Jun-Jie Yang; Ji-Guo Zhang; Yuan-Ru Guo; Shujun Li; Qing-Jiang Pan (Chemical Engineering Journal, 2023)

Formation Mechanism of Thick Coal Seam in the Lower Indus Basin, SE Pakistan - Hassan Nasir Mangi; Ru′an Chi; Jun Zhao; Detian Yan; Lara Sindhu; Dongsheng He; Zixin He; Jing Li; Umar Ashraf; Hongbo Wang (Natural Resources Research, 2023)

Analysis of Whole Blood and Urine Trace Elements in Children with Autism Spectrum Disorders and Autistic Behaviors - Gang Zhao; Si-jin Liu; Xin-yu Gan; Jun-ru Li; Xiao-xue Wu; Si-yan Liu; Yi-si Jin; Ke-rang Zhang; Hong-mei Wu (Biological Trace Element Research, 2023)
The relationship between trace elements and neurological development is an emerging research focus. We performed a case–control study to explore (1) the differences of 13 trace elements chromium (Cr), manganese (Mn), cobalt (Co), zinc (Zn), arsenic (As), selenium (Se), molybdenum (Mo), cadmium (Cd), stannum (Sn), stibium (Sb), mercury (Hg), titanium (TI), and plumbum (Pb) concentration in whole blood and urine between autism spectrum disorder (ASD) children and their typical development peers, and (2) the association between the 13 trace elements and core behaviors of ASD. Thirty ASD subjects (cases) and 30 age-sex-matched healthy subjects from Baise City, Guangxi Zhuang Autonomous Region, China, were recruited. Element analysis was carried out by inductively coupled plasma-optical emission spectrometry. Autistic behaviors were assessed using Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Children Neuropsychological and Behavior Scale (CNBS). The whole blood concentrations of Mo ( p = 0.004), Cd (0.007), Sn ( p = 0.003), and Pb ( p = 0.037) were significantly higher in the ASD cases than in the controls. Moreover, Se (0.393), Hg (0.408), and Mn (− 0.373) concentrations were significantly correlated between whole blood and urine levels in ASD case subjects. There were significant correlations between whole blood Sb (0.406), Tl (0.365), Mo (− 0.4237), Mn (− 0.389), Zn (0.476), and Se (0.375) levels and core behaviors of ASD. Although the mechanism of trace element imbalance in ASD is unclear, these data demonstrate that core behaviors of ASD may be affected by certain trace elements. Further studies are recommended for exploring the mechanism of element imbalance and providing corresponding clinical treatment measures.

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling - Yan Li; Ru Xu; Kun Yang; Yanxu Liu; Shuai Wang; Sha Zhou; Zhao Yang; Xiaoming Feng; Chunyang He; Zhengjie Xu; Wenwu Zhao (Global Change Biology, 2023)
The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP ecosystems for their contribution to precipitation. We found TP ecosystems contributed substantially to local and downwind precipitation, with a contribution of 221 mm/year for the TP and neighboring areas through evapotranspiration (ET) (104 mm/year through transpiration), declined to

Identification of mercury species in coal combustion by-products from power plants using thermal desorption-atomic fluorescence spectrometry on-line coupling system - Kai-Qiang He; Xiao-Ru Zhang; Yuan-Peng Li; Xue-Lei Duan; Yan Li; Yang-Hong Jiang; Xiao-Dong Yuan; Ke-Gang Zhang; Chun-Gang Yuan (Chemosphere, 2023)

Proteomic profiling reveals dysregulated mitochondrial complex subunits responsible for myocardial toxicity induced by SiNPs - Xinying Zhao; Hailin Xu; Yan Li; Ru Ma; Yi Qi; Min Zhang; Caixia Guo; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Taking glucose as intermediate bridge-signal-molecule for on-site and convenient detection of ochratoxin A in rice with portable glucose meter - Ru Zhang; Chao Yan; Ziwen Zong; Wei Qu; Li Yao; Jianguo Xu; Yingyue Zhu; Bangben Yao; Wei Chen (Food Chemistry, 2023)

Narrowing fossil fuel consumption in the Indian road transport sector towards reaching carbon neutrality - M.S. Hossain; Yan Ru Fang; Teng Ma; Chen Huang; Wei Peng; Johannes Urpelainen; Chetan Hebbale; Hancheng Dai (Energy Policy, 2023)

Identifying the impact of Fe nanoparticles encapsulated by nitrogen-doped carbon to Fe single atom sites for boosting oxygen reduction reaction toward Zn-air batteries - Wen-Jun Niu; Ying-Yun Yan; Ru-Ji Li; Wei-Wei Zhao; Jiang-Lei Chen; Ming-Jin Liu; Bingni Gu; Wen-Wu Liu; Yu-Lun Chueh (Chemical Engineering Journal, 2023)

Realizing the bifunctional electrocatalysis via local charge rearrangement of α-CrOOH-modulated Co@CoMoOx for overall water splitting - Suh-Ciuan Lim; Chao-Lung Chiang; Chun-Kuo Peng; Wen-Bin Wu; Yu-Chang Lin; Yu-Ru Lin; Chi-Liang Chen; Yan-Gu Lin (Chemical Engineering Journal, 2023)

Efficient microalgal lipid production driven by salt stress and phytohormones synergistically - Zi-Yan Yang; Kai-Xuan Huang; Yu-Ru Zhang; Lei Yang; Jin-Long Zhou; Qiao Yang; Feng Gao (Bioresource Technology, 2023)

Dissolved organic matter–assisted phytoremediation potential of cotton for Cd-contaminated soil: a relationship between dosage and phytoremediation efficiency - Tao Min; Tong Luo; Hao He; Jie Qin; Yan Wang; Liyang Cheng; Sibo Ru; Junhua Li (Environmental Science and Pollution Research, 2022)

Understanding the molecular mechanism of the effect of ginkgo folium on the treatment of IgA nephropathy using network pharmacology and molecular docking - Xue Ru; Yi Zhang; Yan Gao; Huaikun Wang (Natural Product Research, 2022)

The central role of GmGLP20.4 in root architecture modifications of soybean under low-nitrogen stress - Wei Wang; Jiajia Li; Muhammad Nadeem; Jianxin Wang; Ru Huang; Qian Liu; Wenqiao Fan; Haowei Zheng; Long Yan; Xiaobo Wang (Theoretical and Applied Genetics, 2022)

PITPNC1 promotes the thermogenesis of brown adipose tissue under acute cold exposure - Guoqing Tang; Chengxin Ma; Liangkui Li; Shaoyan Zhang; Fengsheng Li; Jin Wu; Yesheng Yin; Qing Zhu; Yan Liang; Ru Wang; He Huang; Tong-Jin Zhao; et al. (Science China Life Sciences, 2022)
Brown adipose tissue (BAT) plays an essential role in non-shivering thermogenesis. The phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) is identified as a lipid transporter that reciprocally transfers phospholipids between intracellular membrane structures. However, the physiological significance of PITPNC1 and its regulatory mechanism remain unclear. Here, we demonstrate that PITPNC1 is a key player in thermogenesis of BAT. While Pitpnc1 −/− mice do not differ with wildtype mice in body weight and insulin sensitivity on either chow or high-fat diet, they develop hypothermia when subjected to acute cold exposure at 4°C. The Pitpnc1 −/− brown adipocytes exhibit defective β-oxidation and abnormal thermogenesis-related metabolism pathways in mitochondria. The deficiency of lipid mobilization in Pitpnc1 −/− brown adipocytes might be the result of excessive accumulation of phosphatidylcholine and a reduction of phosphatidic acid. Our findings have uncovered significant roles of PITPNC1 in mitochondrial phospholipid homeostasis and BAT thermogenesis.

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Effects of passenger blockage on smoke flow properties in subway station fires - Fan Wu; Yan Wang; Ru Zhou; Juncheng Jiang (Environmental Science and Pollution Research, 2022)

Stachybotranes A–D, phenylspirodrimanes from the wetland fungus Stachybotrys chartarum with cytotoxic activities - Yan-Ru Bao; Han-Lin Feng; Xin-Sheng Yao (Natural Product Research, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Analyzing the mechanism of nitrous oxide production in aerobic phase of anoxic/aerobic sequential batch reactor from the perspective of key enzymes - Rui Yang; Lin-jiang Yuan; Ru Wang; Zhi-xian He; Lin Lei; Yan-chen Ma (Environmental Science and Pollution Research, 2022)

Land development suitability analysis for transport planning evaluation and optimization in mountainous ecological region - Gao-ru Zhu; Man Wang; Qi-li Li; Jie Liu; Yan-ni Zhao; Jia-wei Gao; Hong-lei Xu (Journal of Mountain Science, 2022)

NNMT is induced dynamically during beige adipogenesis in adipose tissues depot-specific manner - Ru Jia; Xiaojing Wei; Jianan Jiang; Zhao Yang; Jiaqi Huang; Jing Liu; Jianqun Yan; Xiao Luo (Journal of Physiology and Biochemistry, 2022)

Association between ambient air pollution and multiple sclerosis: a systemic review and meta-analysis - Chao Tang; Qing-Ru Li; Yan-Mei Mao; Yuan-Rui Xia; Heng-Sheng Guo; Jun-Ping Wang; Zong-Wen Shuai; Dong-Qing Ye (Environmental Science and Pollution Research, 2021)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Expression of the SPL-like gene LaSPL9 in Japanese larch (Larix leptolepis) is regulated by miR156 during somatic embryogenesis - Li-feng Zhang; Yan-ru Fan; Qian Lan; Li-wang Qi; Su-ying Han (Trees, 2021)

Recent progress of oridonin and its derivatives for cancer therapy and drug resistance - Yong-Feng Guan; Xiu-Juan Liu; Xiao-Jing Pang; Wen-Bo Liu; Guang -Xi Yu; Yin -Ru Li; Yan-Bing Zhang; Jian Song; Sai-Yang Zhang (Medicinal Chemistry Research, 2021)

Epigenetics in psoriasis: perspective of DNA methylation - Ying Luo; Keshen Qu; Le Kuai; Yi Ru; Keke Huang; Xiaoning Yan; Meng Xing (Molecular Genetics and Genomics, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Luteolin alleviates ulcerative colitis through SHP-1/STAT3 pathway - Bo-Lin Li; Dan-Yang Zhao; Peng-Li Du; Xiao-Tian Wang; Qian Yang; Yan-Ru Cai (Inflammation Research, 2021)

Molecular epidemiological characteristics of echovirus 6 in mainland China: extensive circulation of genotype F from 2007 to 2018 - Wenjun Cheng; Tianjiao Ji; Shuaifeng Zhou; Yong Shi; Lili Jiang; Yong Zhang; Dongmei Yan; Qian Yang; Yang Song; Ru Cai; Wenbo Xu (Archives of Virology, 2021)
Echovirus 6 (E6) is associated with various clinical diseases and is frequently detected in environmental sewage. Despite its high prevalence in humans and the environment, little is known about its molecular phylogeography in mainland China. In this study, 114 of 21,539 (0.53%) clinical specimens from hand, foot, and mouth disease (HFMD) cases collected between 2007 and 2018 were positive for E6. The complete VP1 sequences of 87 representative E6 strains, including 24 strains from this study, were used to investigate the evolutionary genetic characteristics and geographical spread of E6 strains. Phylogenetic analysis based on VP1 nucleotide sequence divergence showed that, globally, E6 strains can be grouped into six genotypes, designated A to F. Chinese E6 strains collected between 1988 and 2018 were found to belong to genotypes C, E, and F, with genotype F being predominant from 2007 to 2018. There was no significant difference in the geographical distribution of each genotype. The evolutionary rate of E6 was estimated to be 3.631 × 10 -3 substitutions site -1 year -1 (95% highest posterior density [HPD]: 3.2406 × 10 -3 -4.031 × 10 -3 substitutions site -1 year -1 ) by Bayesian MCMC analysis. The most recent common ancestor of the E6 genotypes was traced back to 1863, whereas their common ancestor in China was traced back to around 1962. A small genetic shift was detected in the Chinese E6 population size in 2009 according to Bayesian skyline analysis, which indicated that there might have been an epidemic around that year.

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Nonadditive and Legacy Effects of Spring and Autumn Warming on Soil Respiration in an Old-Field Grassland - Shijie Ning; Jian Song; Jingyi Ru; Zhenxing Zhou; Jiajia Zhang; Xianghui Liu; Yan Hui; Yafei Ma; Shiqiang Wan (Ecosystems, 2021)

MicroRNA‐144 promotes remote limb ischemic preconditioning-mediated neuroprotection against ischemic stroke via PTEN/Akt pathway - Si-Jin Zhong; Miao-Miao Cui; Yu-Ting Gao; Xue-Yan Cao; Bin Chen; Xian-Ru Wen (Acta Neurologica Belgica, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Early-Life Multiple Sevoflurane Exposures Alleviate Long-term Anxiety-Like Behaviors in Mice via the proBDNF/ERK Pathway - Ru-Yi Luo; Cong Luo; Feng Zhong; Wei-Yun Shen; Hui Li; Yan-Ling Zhang; Ru-Ping Dai (Molecular Neurobiology, 2021)

A new cyclic peptide from the fibrous root of Pseudostellaria heterophylla - Xiao-fei Zhao; Qian Zhang; Han-tao Zhao; Yan-da Zhang; Han-ru Liu; Lu-jiang Yuan; Qian-feng Chen (Natural Product Research, 2020)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Rapid identification of landslide, collapse and crack based on low-altitude remote sensing image of UAV - Xu-gang Lian; Zou-jun Li; Hong-yan Yuan; Ji-bo Liu; Yan-jun Zhang; Xiao-yu Liu; Yan-ru Wu (Journal of Mountain Science, 2020)

Novel ACADVL variants resulting in mitochondrial defects in long-chain acyl-CoA dehydrogenase deficiency - Ting Chen; Fan Tong; Xiao-yu Wu; Ling Zhu; Qiu-zi Yi; Jing Zheng; Ru-lai Yang; Zheng-yan Zhao; Xiao-hui Cang; Qiang Shu; Ping-ping Jiang (Journal of Zhejiang University-SCIENCE B, 2020)

Cadmium phytotoxicity, related physiological changes in Pontederia cordata: antioxidative, osmoregulatory substances, phytochelatins, photosynthesis, and chlorophyll fluorescence - Jian-pan Xin; SiSi Ma; Chu Zhao; Yan Li; Ru-nan Tian (Environmental Science and Pollution Research, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Emerging relationship between RNA helicases and autophagy - Miao-miao Zhao; Ru-sha Wang; Yan-lin Zhou; Zheng-gang Yang (Journal of Zhejiang University-SCIENCE B, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Multiplex RT–PCR Assay for the Simultaneous Detection and Identification of Five Sugarcane Viruses - Xiao-Yan Feng; Wen-Zhi Wang; Lin-Bo Shen; Jun-Gang Wang; Guo-Ru Xiong; Cui-Lian Feng; Ting-Ting Zhao; Shu-Zhen Zhang (Sugar Tech, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Synthesis and bioactivities of phenazine-1-carboxylic piperazine derivatives - Fei Han; Ru Yan; Min Zhang; Zhu Xiang; Qinglai Wu; Junkai Li (Natural Product Research, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Effects of small nucleolar RNA SNORD44 on the proliferation, apoptosis and invasion of glioma cells - Xian-Ru Xia; Wen-Cui Li; Zong-Tao Yu; Jie Li; Chun-Yan Peng; Li Jin; Guo-Lin Yuan (Histochemistry and Cell Biology, 2020)

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

Betulinic acid attenuates lipopolysaccharide-induced vascular hyporeactivity in the rat aorta by modulating Nrf2 antioxidative function - Yao-Yao Bai; Dong Yan; Hui-Ying Zhou; Wei-Xin Li; Yang-Yun Lou; Xin-Ru Zhou; Ling-Bo Qian; Chi Xiao (Inflammopharmacology, 2020)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

Overview of pharmacological activities of Andrographis paniculata and its major compound andrographolide - Yan Dai; Shao-Ru Chen; Ling Chai; Jing Zhao; Yitao Wang; Ying Wang (Critical Reviews in Food Science and Nutrition, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Exogenous application of gibberellic acid and ascorbic acid improved tolerance of okra seedlings to NaCl stress - Yong-Hui Wang; Gen Zhang; Yuan Chen; Jin Gao; Yan-Ru Sun; Ming-Fa Sun; Jian-Ping Chen (Acta Physiologiae Plantarum, 2019)

De novo assembly of white poplar genome and genetic diversity of white poplar population in Irtysh River basin in China - Yan-Jing Liu; Xiao-Ru Wang; Qing-Yin Zeng (Science China Life Sciences, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

LaMIR166a-mediated auxin biosynthesis and signalling affect somatic embryogenesis in Larix leptolepis - Zhe-Xin Li; Yan-Ru Fan; Shao-Fei Dang; Wan-Feng Li; Li-Wang Qi; Su-ying Han (Molecular Genetics and Genomics, 2018)

Molecular and morphological data reveals new insights into genetic diversity and population structure of Chinese cherry (Prunus pseudocerasus Lindl.) landraces - Tao Chen; Yue-yang Hu; Qing Chen; Yan Wang; Jing Zhang; Hao-ru Tang; Xiao-rong Wang (Genetic Resources and Crop Evolution, 2018)

Cyproheptadine Regulates Pyramidal Neuron Excitability in Mouse Medial Prefrontal Cortex - Yan-Lin He; Kai Wang; Qian-Ru Zhao; Yan-Ai Mei (Neuroscience Bulletin, 2018)

Application of Phragmites australis to remove phenol from aqueous solutions by chemical activation in batch and fixed-bed columns - Sheng-Li Shi; Jun-Ping Lv; Qi Liu; Fang-Ru Nan; Xiao-Yan Jiao; Jia Feng; Shu-Lian Xie (Environmental Science and Pollution Research, 2018)

Scopuquinolone B, a new monoterpenoid dihydroquinolin-2(1 H )-one isolated from the coral-derived Scopulariopsis sp. fungus - Xiao-Feng Mou; Xin Liu; Ru-Fang Xu; Mei-Yan Wei; Yao-Wei Fang; Chang-Lun Shao (Natural Product Research, 2018)

Over-expression of the Arabidopsis formate dehydrogenase in chloroplasts enhances formaldehyde uptake and metabolism in transgenic tobacco leaves - Ru Wang; Zhidong Zeng; Hongxia Guo; Hao Tan; Ang Liu; Yan Zhao; Limei Chen (Planta, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

CAT and MDH improve the germination and alleviate the oxidative stress of cryopreserved Paeonia and Magnolia pollen - Meng Xue Jia; Xue Ru Jiang; Jin Xu; Wei Di; Yin Shi; Yan Liu (Acta Physiologiae Plantarum, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Spatial distribution modeling of temperature increase for the uplifted mountain terrains and its characteristics in Southwest China - Yan-xia Wang; Kun Ding; Mao-biao Li; Ru-liang Zhou (Journal of Mountain Science, 2017)

Calcium controls the formation of vacuoles from mitochondria to regulate microspore development in wheat - Dong Xiao Li; Hai Yan Hu; Gan Li; Zhen Gang Ru; Hui Qiao Tian (Plant Reproduction, 2017)

PCL/β-TCP Composite Scaffolds Exhibit Positive Osteogenic Differentiation with Mechanical Stimulation - So Hee Park; Su A. Park; Yun Gyeong Kang; Ji Won Shin; Young Shik Park; Seo Rin Gu; Yan Ru Wu; Jie Wei; Jung-Woog Shin (Tissue Engineering and Regenerative Medicine, 2017)

Mechanical stimuli modulate intracellular calcium oscillations: a pathological model without chemical cues - Yan Ru Wu; Yun Gyeong Kang; Ji Won Shin; Mi Jin Kim; Jung-Woog Shin (Biotechnology Letters, 2017)

ROS-induced oxidative stress is closely related to pollen deterioration following cryopreservation - Meng Xue Jia; Yin Shi; Wei Di; Xue Ru Jiang; Jin Xu; Yan Liu (In Vitro Cellular & Developmental Biology - Plant, 2017)

Effects of xeric shrubs on soil microbial communities in a desert in northern China - Yanfei Sun; Yuqing Zhang; Wei Feng; Shugao Qin; Zhen Liu; Yuxuan Bai; Ru Yan; Keyu Fa (Plant and Soil, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes - Xue-Ru Liu; Lu Cao; Tao Li; Lin-Lin Chen; Yi-Yan Yu; Wen-Jun Huang; Li Liu; Xiao-Qiu Tan (Apoptosis, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Applying the strategy of light environment control to improve the biomass and polysaccharide production of Nostoc flagelliforme - Pei-pei Han; Shi-gang Shen; Hui-Yan Wang; Shun-yu Yao; Zhi-lei Tan; Cheng Zhong; Shi-ru Jia (Journal of Applied Phycology, 2017)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

Temporal properties of dual-peak responses of mouse retinal ganglion cells and effects of inhibitory pathways - Ru-Jia Yan; Hai-Qing Gong; Pu-Ming Zhang; Shi-Gang He; Pei-Ji Liang (Cognitive Neurodynamics, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco - Jun-Ru Hu; Yan-Hua Huang; Guo-Xia Wang; Ying-Xia Wu; Jian-An Xian; An-Li Wang; Jun-Ming Cao (Fish Physiology and Biochemistry, 2016)

Establishment of Salvia castanea Diels f. tomentosa Stib. hairy root cultures and the promotion of tanshinone accumulation and gene expression with Ag+, methyl jasmonate, and yeast extract elicitation - Bo Li; Bangqing Wang; Hongyan Li; Liang Peng; Mei Ru; Zongsuo Liang; Xijun Yan; Yonghong Zhu (Protoplasma, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Model-based meta-analysis of the effects of non-selective and α1-selective GABAA receptor agonists in healthy volunteers - Yu-Peng Ren; Ru-Jia Xie; Scott Marshall; Liang Li; Tian-Yan Zhou; Wei Lu (European Journal of Clinical Pharmacology, 2015)

Investigation on time-dependent behaviour and long-term stability of underground water-sealed cavern - Huan-ling Wang; Wei-ya Xu; Long Yan; Qing-xiang Meng; Ru-bin Wang; Hai-bin Zhao; Wei-chau Xie (European Journal of Environmental and Civil Engineering, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Potent Antifouling Marine Dihydroquinolin-2(1H)-one-Containing Alkaloids from the Gorgonian Coral-Derived Fungus Scopulariopsis sp. - Chang-Lun Shao; Ru-Fang Xu; Chang-Yun Wang; Pei-Yuan Qian; Kai-Ling Wang; Mei-Yan Wei (Marine Biotechnology, 2015)

Comparison of bacterial community structures of terrestrial cyanobacterium Nostoc flagelliforme in three different regions of China using PCR-DGGE analysis - Pei-pei Han; Shi-gang Shen; Shi-ru Jia; Hui-yan Wang; Cheng Zhong; Zhi-lei Tan; He-xin Lv (World Journal of Microbiology and Biotechnology, 2015)

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

Combined characteristics of drought on multiple time scales in Huang-Huai-Hai River basin - Ru Huang; Denghua Yan; Shaohua Liu (Arabian Journal of Geosciences, 2015)

Efficient secretory production of CotA-laccase and its application in the decolorization and detoxification of industrial textile wastewater - Zheng-Bing Guan; Yan Shui; Chen-Meng Song; Ning Zhang; Yu-Jie Cai; Xiang-Ru Liao (Environmental Science and Pollution Research, 2015)

Using fluorescence spectroscopy coupled with chemometric analysis to investigate the origin, composition, and dynamics of dissolved organic matter in leachate-polluted groundwater - Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Lei Wang; Yan Ma; Dong-Yu Cui; Wen-Bing Tan (Environmental Science and Pollution Research, 2015)

Augmenter of liver regeneration plays a protective role against hydrogen peroxide-induced oxidative stress in renal proximal tubule cells - Ning Xia; Ru-yu Yan; Qi Liu; Xiao-hui Liao; Hang Sun; Hui Guo; Ling Zhang (Apoptosis, 2015)

The relationship between the plant-encoded RNA-dependent RNA polymerase 1 and alternative oxidase in tomato basal defense against Tobacco mosaic virus - Yang-Wen-Ke Liao; Ya-Ru Liu; Jia-Yang Liang; Wen-Ping Wang; Jie Zhou; Xiao-Jian Xia; Yan-Hong Zhou; Jing-Quan Yu; Kai Shi (Planta, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Ligand-based 3D pharmacophore design, virtual screening and molecular docking for novel p38 MAPK inhibitors - Lijuan He; Ru Dai; Xuan R. Zhang; Si Y. Gao; Yan Y. He; Li B. Wang; Xang Gao; Lu Q. Yang (Medicinal Chemistry Research, 2015)

A novel strategy for rapid quantification of 20( S )-protopanaxatriol and 20( S )-protopanaxadiol saponins in Panax notoginseng P. ginseng and P. quinquefolium - Fa-Xiang Xu; Cen Yuan; Jian-Bo Wan; Ru Yan; Hao Hu; Shao-Ping Li; Qing-Wen Zhang (Natural Product Research, 2015)

Nutrients and non-volatile taste compounds in Chinese mitten crab by-products - Yan-Ru Guo; Sai-Qi Gu; Xi-Chang Wang; Ke-Jin Zhuang; Shuai Wang; Jing Shi (Fisheries Science, 2015)

Inactivation of FoxM1 transcription factor contributes to curcumin-induced inhibition of survival, angiogenesis, and chemosensitivity in acute myeloid leukemia cells - Jing-ru Zhang; Fei Lu; Ting Lu; Wen-hao Dong; Peng Li; Na Liu; Dao-xin Ma; Chun-yan Ji (Journal of Molecular Medicine, 2014)

A study of shear strength properties of municipal solid waste in Chongqing landfill, China - Yan Ru Zhao; Qiang Xie; Gui Lin Wang; Yong Jian Zhang; Yong Xing Zhang; Wenjun Su (Environmental Science and Pollution Research, 2014)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

The role of epithelial tight junctions involved in pathogen infections - Ru-Yi Lu; Wan-Xi Yang; Yan-Jun Hu (Molecular Biology Reports, 2014)

Cloning and characterisation of a pepper aquaporin, CaAQP, which reduces chilling stress in transgenic tobacco plants - Yan-Xu Yin; Wei-Li Guo; Ying-Li Zhang; Jiao-Jiao Ji; Huai-Juan Xiao; Fei Yan; Yan-Yan Zhao; Wen-Chao Zhu; Ru-Gang Chen; Wei-Guo Chai; Zhen-Hui Gong (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Analysis of aroma-active compounds in three sweet osmanthus (Osmanthus fragrans) cultivars by GC-olfactometry and GC-MS - Xuan Cai; Rong-zhang Mai; Jing-jing Zou; Hong-yan Zhang; Xiang-ling Zeng; Ri-ru Zheng; Cai-yun Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Comparison of fatty acid and amino acid profiles of steamed Chinese mitten crab - Yan-Ru Guo; Sai-Qi Gu; Xi-Chang Wang; Lin-Min Zhao; Jin-Yuan Zheng (Fisheries Science, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Characterization of S-(+)-linalool synthase from several provenances of Cinnamomum osmophloeum - Yan-Liang Lin; Yi-Ru Lee; Wen-Ke Huang; Shang-Tzen Chang; Fang-Hua Chu (Tree Genetics & Genomes, 2014)

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning - Hao Chen; Li Yang; Yan Xu; Guang-yan Wu; Juan Yao; Jun Zhang; Zhi-ru Zhu; Zhi-an Hu; Jian-feng Sui; Bo Hu (The Cerebellum, 2014)

Development and Characterisation of Ursolic Acid Nanocrystals Without Stabiliser Having Improved Dissolution Rate and In Vitro Anticancer Activity - Ju Song; Yancai Wang; Yuelin Song; Hokman Chan; Chao Bi; Xiao Yang; Ru Yan; Yitao Wang; Ying Zheng (AAPS PharmSciTech, 2014)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Comparison of the dissipation behaviour of three neonicotinoid insecticides in tea - Ru-Yan Hou; Jin-Feng Hu; Xiao-San Qian; Ting Su; Xiao-Hui Wang; Xiu-Xia Zhao; Xiao-Chun Wan (Food Additives & Contaminants: Part A, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Analysis of average standardized SSR allele size supports domestication of soybean along the Yellow River - Ying-hui Li; Chen Zhang; Marinus J. M. Smulders; Wei Li; Yan-song Ma; Qu Xu; Ru-zhen Chang; Li-juan Qiu (Genetic Resources and Crop Evolution, 2013)

Trends of precipitation extremes during 1960–2008 in Xinjiang, the Northwest China - Feng-qing Jiang; Ru-Ji Hu; Shao-Ping Wang; Yan-Wei Zhang; Li Tong (Theoretical and Applied Climatology, 2013)

A simple method to prepare magnetic modified beer yeast and its application for cationic dye adsorption - Jun-Xia Yu; Li-Yan Wang; Ru-An Chi; Yue-Fei Zhang; Zhi-Gao Xu; Jia Guo (Environmental Science and Pollution Research, 2013)

Cloning and sequence analysis of chitin synthase gene fragments of Demodex mites - Ya-e Zhao; Zheng-hang Wang; Yang Xu; Ji-ru Xu; Wen-yan Liu; Meng Wei; Chu-ying Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Expression, purification, and evaluation for anticancer activity of ribosomal protein L31 gene (RPL31) from the giant panda (Ailuropoda melanoleuca) - Xiu-Lan Su; Yi-Ling Hou; Xiang-Hui Yan; Xiang Ding; Wan-Ru Hou; Bing Sun; Si-Nan Zhang (Molecular Biology Reports, 2012)

Role of ROS/RhoA/PI3K/PKB Signaling in NS1619-Mediated Blood–Tumor Barrier Permeability Increase - Yan-Ting Gu; Yi-Xue Xue; Yan-Feng Wang; Jin-Hui Wang; Qian-Ru ShangGuan; Jia-Xu Zhang; Li-Juan Qin (Journal of Molecular Neuroscience, 2012)

The mitochondrial genome of the quiet-calling katydids, Xizicus fascipes (Orthoptera: Tettigoniidae: Meconematinae) - MING RU YANG; ZHI JUN ZHOU; YAN LIN CHANG; LE HONG ZHAO (Journal of Genetics, 2012)

Lead and cadmium-induced oxidative stress impacting mycelial growth of Oudemansiella radicata in liquid medium alleviated by microbial siderophores - Yan-ru Cao; Xi-yu Zhang; Jia-yu Deng; Qi-qi Zhao; Heng Xu (World Journal of Microbiology and Biotechnology, 2012)

Effect of heavy metal-solubilizing microorganisms on zinc and cadmium extractions from heavy metal contaminated soil with Tricholoma lobynsis - Ling-yun Ji; Wei-wei Zhang; Dong Yu; Yan-ru Cao; Heng Xu (World Journal of Microbiology and Biotechnology, 2012)

Variations and trends of onset, cessation and length of climatic growing season over Xinjiang, NW China - Feng-qing Jiang; Ru-ji Hu; Yan-wei Zhang; Xue-mei Li; Li Tong (Theoretical and Applied Climatology, 2011)

QTL mapping of bio-energy related traits in Sorghum - Yan-an Guan; Hai-lian Wang; Ling Qin; Hua-wen Zhang; Yan-bing Yang; Feng-ju Gao; Ru-yu Li; Hong-gang Wang (Euphytica, 2011)

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis - Jin-Ran Dai; Bing Liu; Dong-Ru Feng; Hai-yan Liu; Yan-ming He; Kang-biao Qi; Hong-Bin Wang; Jin-Fa Wang (Plant Cell Reports, 2011)

Effect of neuronal excitotoxicity on Munc18-1 distribution in nuclei of rat hippocampal neuron and primary cultured neuron - Yan-Ping Zhang; Ping Wan; Hong-Quan Wang; Hong Zhao; Yu-Xia Xu; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2011)

BRAF V600E mutation and resistance to anti-EGFR monoclonal antibodies in patients with metastatic colorectal cancer: a meta-analysis - Chen Mao; Ru-Yan Liao; Li-Xin Qiu; Xi-Wen Wang; Hong Ding; Qing Chen (Molecular Biology Reports, 2011)

MeJA-inducible expression of the heterologous JAZ2 promoter from Arabidopsis in Populus trichocarpa protoplasts - Yin Wang; Guan-Jun Liu; Xiu-Feng Yan; Zhi-Gang Wei; Zhi-Ru Xu (Journal of Plant Diseases and Protection, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Evaluation of seed storage-protein gene 5′ untranslated regions in enhancing gene expression in transgenic rice seed - Wen Xian Liu; Hua Liang Liu; Zhi Jian Chai; Xiu Ping Xu; Yan Ru Song; Le Qing Qu (Theoretical and Applied Genetics, 2010)

TGFBR1*6A/9A polymorphism and cancer risk: a meta-analysis of 13,662 cases and 14,147 controls - Ru-Yan Liao; Chen Mao; Li-Xin Qiu; Hong Ding; Qing Chen; Hai-Feng Pan (Molecular Biology Reports, 2010)

Stearoyl-CoA Desaturase (SCD) Gene Polymorphism in Goat Breeds - Chun-Lei Zhang; Xue-Yuan Gao; Ru-Ying Shao; Yan-Hong Wang; Xing-Tang Fang; Hong Chen (Biochemical Genetics, 2010)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

Glutamate enhances the surface distribution and release of Munc18 in cerebral cortical neurons - Ping Wan; Yan-Ping Zhang; Jie Yan; Yu-Xia Xu; Hong-Quan Wang; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2010)

Detection of circulating tumor cells in peripheral blood from patients with gastric cancer using microRNA as a marker - Hui Zhou; Jun-Ming Guo; Yan-Ru Lou; Xin-Jun Zhang; Fa-De Zhong; Zhen Jiang; Jia Cheng; Bing-Xiu Xiao (Journal of Molecular Medicine, 2010)

A Series of Novel Rare Earth Molybdotungstosilicate Heteropolyoxometalates Binding to Bovine Serum Albumin: Spectroscopic Approach - Yan-Jun Hu; Yu Ou-Yang; Ai-Min Bai; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Biological Activation of Heteropoly Complex of Molybdotungstosilicate Containing Lanthanum K10H3La(SiMo6W5O39)2⋅26H2O: Spectroscopic Approach and Microcalorimetry - Yan-Jun Hu; Yu Ou-Yang; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

cDNA, genomic sequence cloning and overexpression of ribosomal protein S25 gene (RPS25) from the Giant Panda - Yan-zhe Hao; Wan-ru Hou; Yi-ling Hou; Yu-jie Du; Tian Zhang; Zheng-song Peng (Molecular Biology Reports, 2009)

Studying the Interaction of Pirarubicin with DNA and Determining Pirarubicin in Human Urine Samples: Combining Excitation -Emission Fluorescence Matrices with Second-order Calibration Methods - Hong-Yan Zou; Hai-Long Wu; Yan Zhang; Shu-Fang Li; Jin-Fang Nie; Hai-Yan Fu; Ru-Qin Yu (Journal of Fluorescence, 2009)

Use of simple sequence repeats for authentication of sugarcane hybrids generated from Yunnan Erianthus rockii - Yan-Fen Jing; Lian-an Tao; Xin-long Liu; Ru-dong An; Xue-kuan Chen (Sugar Tech, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

Competitive displacement of the native species Bursaphelenchus mucronatus by an alien species Bursaphelenchus xylophilus (Nematoda: Aphelenchida: Aphelenchoididae): a case of successful invasion - Xin-Yue Cheng; Pei-Zhen Xie; Fei-Xue Cheng; Ru-Mei Xu; Bing-Yan Xie (Biological Invasions, 2009)

Synergistic up-regulation of muscle LIM protein expression in C2C12 and NIH3T3 cells by myogenin and MEF2C - Zhen-Xing Ji; Chao Du; Guo-Sheng Wu; Shu-Yan Li; Guo-Shun An; Yu-Xi Yang; Ru Jia; Hong-Ti Jia; Ju-Hua Ni (Molecular Genetics and Genomics, 2009)

Overexpression of lentivirus-mediated glial cell line-derived neurotrophic factor in bone marrow stromal cells and its neuroprotection for the PC12 cells damaged by lactacystin - Ya-Ru Su; Jian Wang; Jian-Jun Wu; Yan Chen; Yu-Ping Jiang (Neuroscience Bulletin, 2007)

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)

Hypoxic postconditioning enhances the survival and inhibits apoptosis of cardiomyocytes following reoxygenation: role of peroxynitrite formation - Hai-Chang Wang; Hai-Feng Zhang; Wen-Yi Guo; Hui Su; Kun-Ru Zhang; Qiu-Xia Li; Wenli Yan; Xin L. Ma; Bernard L. Lopez; Theodore A. Christopher; Feng Gao (Apoptosis, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Treatment and follow-up of children with transient congenital hypothyroidism - Ru-lai Yang; Zhi-wei Zhu; Xue-lian Zhou; Zheng-yan Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

Distribution of mercury in typical wetland plants in the Sanjiang plain - Ru-hai Liu; Qi-chao Wang; Yan Wang; Lei Zhang; Zhi-guo Shao (Chinese Geographical Science, 2003)

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)

Long-term culture of murine bone-marrow-derived endothelial cells - Qi Ru Wang; Yan Yan; Bao He Wang; Wei Min Li; Norman S. Wolf (In Vitro Cellular & Developmental Biology - Animal, 1998)